Penerapan Model Pembelajaran Two Stay Two Stray Untuk Meningkatkan Kemampuan Memahami Teks Naratif Berbahasa Arab - Mazidatulfaizah Mazidatulfaizah (Institut Agama Islam Negeri Kediri, 2021)
Abstract: This study aims to describe the improvement of students' comprehension skills in Arabic texts by implementing the Two Stay Two Stray learning model in class X IPA MA Al-Anwar Jombang. Design of this research is classroom action research. This action research has four procedures in its implementation, planning, implementing action, observing, and reflecting. The research subjectsvwere students of class X IPA MA Al-Anwar Jombang, 36 students. This research was conducted in January-February 2020 with 2 cycles. Research data in the form of observations, field notes, interviews, test results, and documentation. Data analysis used quantitative description analysis and qualitative description analysis. The criterion for the success of the action is an increase in students' ability to understand Arabic texts. The results obtained after the implementation of the action, namely students become more active and enthusiastic in participating in learning. Students show high attitudes, interests, and enthusiasm. In addition, there is an increase in students' abilities which are shown through test results. The results of student test scores at the time of pre-action that met the KKM standard were 11 people or 31 percent of the total number of students. In the first cycle of activities, 19 students reached the KKM or 53 percent of the total number of students. In cycle II, 28 students reached the KKM or 78 percent of the total number of students. This shows that the Two Stay Two Stray learning model can improve students' ability to understand Arabic texts. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan memahami siswa dalam teks berbahasa Arab dengan implementasi model pembelajaran Two Stay Two Stray pada siswa kelas X IPA MA Al-Anwar Jombang. Desain penelitian ini adalah penelitian tindakan kelas. Penelitian tindakan ini memiliki empat prosedur dalam pelaksanaannya, yaitu perencanaan, implementasi tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas X IPA MA Al-Anwar Jombang yang berjumlah 36 siswa. Penelitian ini dilaksanakan pada bulan Januari-Februari 2020 dengan 2 siklus. Data penelitian berupa hasil observasi, catatan lapangan, hasil wawancara, hasil tes, dan dokumentasi. Analisis data menggunakan analisis deskripsi kuantitatif dan analisis deskripsi kualitatif. Kriteria keberhasilan tindakan yaitu terjadinya peningkatan kemampuan siswa dalam memahami teks berbahasa Arab. Hasil penelitian yang diperoleh setelah implementasi tindakan, yaitu siswa menjadi lebih aktif dan antusias dalam mengikuti pembelajaran. Siswa menujukkan sikap, minat, dan semangat yang tinggi. Selain itu, ada peningkatan kemampuan siswa yang ditunjukkan melalui hasil tes. Hasil skor tes siswa pada saat pratindakan yang memenuhi standar KKM sebanyak 11 orang atau sebesar 31% dari jumlah siswa. Pada kegiatan siklus I, siswa yang mencapai KKM sebanyak 19 orang atau sebesar 53 persen dari jumlah siswa. Pada siklus II, siswa yang mencapai KKM sebanyak 28 orang atau sebesar 78 persen dari jumlah siswa. Hal tersebut 137 menunjukkan bahwa model pembelajaran Two Stay Two Stray dapat meningkatkan kemampuan siswa dalam memahami teks bahasa Arab.